Gait and Clinical Improvements with a Novel Knee Brace for Knee OA - Johnson, Aaron J.; Starr, Roland; Kapadia, Bhaveen H.; Bhave, Anil; Mont, Michael A. (The Journal of Knee Surgery, 2013)
Introduction Knee osteoarthritis causes debilitating pain, and results in characteristic gait changes. Some authors believe that a system of neuromuscular retraining may improve these parameters. We therefore evaluated a novel brace that combines pneumatic joint unloading and active swing-assist to assess: (1) differences in pain levels or medication usage; (2) reductions in additional interventions; (3) changes in quadriceps muscle strength; and (4) improvements in specific gait measurements after 3 months.Patients and methods A prospective pilot series of 10 knee osteoarthritis patients who had exhausted other nonoperative treatment measures were enrolled. These patients were compared with the previous 15 knee osteoarthritis patients who met similar criteria, but were not braced. Quadriceps muscle strength was measured, as were pain levels, and additional interventions such as injections or total knee arthroplasty procedures. Gait parameters measured included: walking speed, total range-of-motion, knee flexion at foot-strike, and knee adduction moment.Results All but one of the compliant patients reported a decrease of at least two pain points after 3 months of use. There was one additional intervention in the brace cohort versus a statistical increase of 10 in the nonbrace cohort. All patients who were compliant with the brace showed an increase in thigh girth measurements, compared with none in the nonbrace cohort. Braced patients experienced retained improvements in at least one gait parameter including improved walking speed, total range of motion, and improved knee-angle at heel strike. The mean improvement in knee adduction moment was a decrease of 0.2255 Nm/kg (range, 0.56 to 0.564 Nm/kg), showing a mean improvement of 48% (range, 16 to 76% of original peak moment).Conclusions The use of a brace that has features including a combination of unloader characteristics along with active swing-assist, provided neuromuscular retraining benefits for patients who have knee osteoarthritis. In summary, although quite encouraging, future larger scale and prospective randomized studies need to assess the potential benefits of this brace for treating knee osteoarthritis.Level of evidence Level II
Keywords: knee; osteoarthritis; TKA; bracing; neuromuscular retraining